2010
DOI: 10.1161/circheartfailure.109.867747
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin B in Heart Failure

Abstract: Background-Chromogranin B (CgB) is a member of the granin protein family. Because CgB is often colocalized with chromogranin A (CgA), a recently discovered cardiac biomarker, we hypothesized that CgB is regulated during heart failure (HF) development. Methods and Results-CgB regulation was investigated in patients with chronic HF and in a post-myocardial infarction HF mouse model. Animals were phenotypically characterized by echocardiography and euthanized 1 week after myocardial infarction. CgB mRNA levels we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 44 publications
2
14
1
Order By: Relevance
“…As previously reported for chromogranins [6], [17], SgII immunoreactivity was evident in cardiomyocytes, however, we also found SgII immunoreactivity in endothelial cells, fibroblasts, and other infiltrative cells of the border zone and the infarcted area (Figure 2B). The production of SgII in several cell types of the myocardium was validated by demonstrating similar SgII mRNA levels in fractions of cardiomyocytes, endothelial cells, and non-cardiomyocyte, non-endothelial cells (Figure 2C).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As previously reported for chromogranins [6], [17], SgII immunoreactivity was evident in cardiomyocytes, however, we also found SgII immunoreactivity in endothelial cells, fibroblasts, and other infiltrative cells of the border zone and the infarcted area (Figure 2B). The production of SgII in several cell types of the myocardium was validated by demonstrating similar SgII mRNA levels in fractions of cardiomyocytes, endothelial cells, and non-cardiomyocyte, non-endothelial cells (Figure 2C).…”
Section: Resultssupporting
confidence: 89%
“…As evaluated by receiver operating analysis, circulating levels of SgII were more closely regulated in HF than both CgA (AUC = 0.84 for SgII vs. AUC = 0.57 for CgA, p = 0.001) and CgB levels (AUC = 0.68 for CgB, p = 0.03 vs. SgII). Use of a proton pump inhibitor (PPI), a medication known to increase circulating CgA levels [6], did not increase SgII levels as levels in patients using PPI (n = 8) were similar to SgII levels in the other HF patients: 0.16 (Q1–3 0.13–0.19) vs. 0.16 (0.14–0.18) nmol/L, respectively, p = 0.68).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Overall, this study illustrated that CpG methylation levels are under genetic control, providing a framework for the study of the molecular mechanisms underlying these processes, while also contributing to the understanding of the interrelation between the regulation of CpG methylation and pathophysiological cardiac phenotypes and biomarkers in the rat (Johnson et al, 2014). For instance, the team reported significant correlation between a locus-specific CpG methylation change in cardiac tissue and levels of serum chromogranin B, which is a correlate of sympathetic nervous system overactivity and has been proposed as a biomarker for heart failure (Røsjø et al, 2010). …”
Section: Landmark Integrative Genomics Studies In the Ratmentioning
confidence: 99%
“…6 Carrying forward the research on CGB in HF, these authors found increased circulating plasma CGB levels in HF patients that correlate with HF disease severity assessed by New York Heart Association (NYHA) functional class. In this context, CGB might not only become a novel target for specific therapeutic interventions but may as well aid in diagnosis and treatment of HF patients in its function as cardiac biomarker.…”
mentioning
confidence: 99%